Randomised Ambulatory Management of Primary Pneumothorax (RAMPP): protocol of an open-label, randomised controlled trial. Issue 1 (11th April 2019) - Hallifax, Rob; Laskawiec-Szkonter, Magda; Dobson, Melissa; Gerry, Stephen; Miller, Robert F; Harvey, John E; Rahman, Najib
Abstract : Introduction: Pneumothorax is a common clinical problem. Primary spontaneous pneumothorax (PSP) occurs in otherwise fit young patients, but optimal management is not clearly defined and often results in a long hospital stay. Ambulatory treatment options are available, but the existing data on their efficacy are poor. The Randomised Ambulatory Management of Primary Pneumothorax trial is a multicentre, randomised controlled trial comparing ambulatory management with standard care, specifically designed to safely and effectively reduce hospital stay. Methods and analysis: 236 patients with PSP will be recruited from UK hospitals. Patients will be randomised 1:1 to treatment to either the 'Intervention' arm (ambulatory device; Rocket Pleural Vent) or the 'Control' arm (aspiration ± standard chest drain insertion). Patients will be followed up for a total of 12 months to assess recurrence rates. The primary outcome is total length of stay in hospital (including readmissions) up to 30 days postrandomisation. The secondary outcomes are pain and breathlessness scores, air leak measurement and radiological evidence (on CT scanning) of emphysema-like changes, compared with short-term and long-term outcomes, respectively, and health economic analysis. Ethics and dissemination: The trial has received ethical approval from the National Research Ethics Service Committee South-Central Oxford A (15/SC/0240). Trial registration number: ISRCTN79151659